Developing enterprise social software in China : insights from Mingdao - Le-Nguyen, Khuong; Guo, Yue, active 2016; Qiong, Jia (London : Palgrave MacMillan UK, 2017)
Cloud-computing and Web 2.0 technologies have triggered a new wave of IT infrastructure adoption, which has been radically changing the way we live and work. In particular, Enterprise 2.0 and Enterprise Social Software (ESS) are getting more attention from organizations worldwide as they help staff to work and collaborate more efficiently. Mingdao that provides an ESS platform via the SaaS delivery model. The case explains the platform's early tortuous design and development, defined its business and revenue model, and improved its platform's various functions and features. Such organizational experiences not only reflect the opportunities and challenges of the ESS market in China, but also present a new way of communication, collaboration, and sharing on the enterprise social network platform.
Originally Published InLe-Nguyen, K., Guo, Y., & Qiong, J. (2017). Developing enterprise social software in China: Insights from Mingdao. Journal of Information Technology Teaching Cases, 7, 62–78.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Management -- Communication systems; Online social networks -- China